Renal sinus fat volume on computed tomography in middle-aged patients at risk for cardiovascular disease and its association with coronary artery calcification. (March 2016) - Murakami, Yoko; Nagatani, Yukihiro; Takahashi, Masashi; Ikeda, Mitsuru; Miyazawa, Itsuko; Morino, Katsutaro; Ohkubo, Takayoshi; Maegawa, Hiroshi; Nitta, Norihisa; Sakai, Hiroshi; Nota, Hiromitsu; Ushio, Noritoshi; et al.
Abstract: Objective: Renal sinus fat (RSF) behaves as one of the perivascular fats, however RSF volume (RSFV) is considerably affected by visceral adipose tissue volume (VTAV). The ratio of RSFV to VATV (RSFV/VATV ratio) can be an index of regional perivascular fat accumulation corrected for the influence of VATV. The aim of this study was to investigate the relation between RSFV/VATV ratio and coronary artery calcium (CAC) in patients with suspected coronary artery disease. Methods: One hundred and eighty-nine patients (mean age 66.7 ± 10.2; 72% men) underwent ECG-gated cardiac computed tomography (CT) and unenhanced abdominal CT. CAC score (CACS) was assessed using axial CT images. RSFV was measured by partially manipulated segmentation of the right kidney. VATV was automatically quantified in the upper abdomen. Logistic and correlation analyses were performed to examine the correlations between CAC, RSFV/VATV ratio, and risk factors of cardiovascular diseases in total and subgroups classified by the patients' age. Results: Log-transformed RSFV/VATV ratio was associated with CAC presence in 112 middle-aged patients less than 69 years of age as well as total. This association remained significant after multivariate adjustment only in the middle-aged patients (OR 15.9, 95% CI 1.15–218.8). In total, RSFV/VATV ratio ( r  = 0.228, p = 0.002) and age ( r  = 0.316, p < 0.001) correlated with CACS on univariate analyses, but only age correlated on multivariate analyses. RSFV/VATV ratio correlated with CACS in the middle-aged patients ( r  = 0.418, p < 0.001), as well as on multivariate analyses. Conclusions: We demonstrated that RSFV/VATV could be an independent risk indicator of CAC in the middle-aged patients. Graphical abstract: Highlights: We examine the association between renal sinus fat volume (RSFV) and CAC. RSF correlated moderately with VATV and weakly with baPWV. The ratio of RSFV to visceral fat volume (RSFV/VATV ratio) is associated with CAC. RSFV/VATV ratio could be a surrogate indicator of CAC in middle-aged patients.